ACCELERATED TESTS FOR DETERMINING THE SPEED OF CORROSION OF STEEL EMBEDDED CONCRETE - Pizarro Cabrera, Raúl (2006)
The results have permitted to evaluate agressive agents from the industrial enviroment (NaHS03) and marine enviroment (sea water). They resulted in a loss of weight in the concrete steel engrossed.